استجابة الاقتصاد الكلي لصدمة في الانفاق الحكومي - صقر, محمد; علي, حسين; درويش, هنادي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study includes analysis of the impact of public spending shocks in Syria on economic activity during the period (1980-2010) and the researcher uses the VAR model (Vector Auto Regression Models) , Impulse response functions and also analysis of variance (Variance decomposition). This study shows that the shock occurrence by 1% in public spending had a positive significant effect on each of the GDP , the total investment and the total consumption during the response period, while it was small as a result of the weakness of the use of public spending policy to influence the conditions of the Syrian economy. On the other hand, there is a lack of coordination between macro-economic policies to achieve general objectives. تناول البحث الحالي دراسة أثر صدمات الانفاق العام في سورية على النشاط الاقتصادي خلال الفترة (1980-2010) باستخدام نموذج VAR (Vector Auto Regression Models) ودوال الاستجابة الدفعية (Impulse response functions) وأيضاً تحليل التباين (Variance decomposition) لسلسلة بيانات سنوية للاقتصاد السوري صادرة عن المكتب المركزي للإحصاء، فتبين أن حدوث صدمة بمقدار 1% في الانفاق العام كان له تأثيراً ايجابياً معنوياً على كل من الناتج المحلي الاجمالي والاستثمار الكلي والاستهلاك الكلي خلال فترة الاستجابة، في حين كانت هذه التأثيرات صغيرة نتيجة غياب حسن استخدام السياسة الانفاقية العامة بما يتناسب مع كل مرحلة والظروف التي مر بها الاقتصاد السوري، إلى جانب ضعف التنسيق بين السياسات الاقتصادية الكلية في سبيل تحقيق الأهداف العامة.